2004
DOI: 10.1161/01.atv.0000118275.60121.2b
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 Is an Essential Inflammatory Mediator in Angiotensin II-Induced Progression of Established Atherosclerosis in Hypercholesterolemic Mice

Abstract: Objective-Chronic inflammatory processes might be involved in the progression and destabilization of atherosclerotic plaques. Therefore, identification of the mechanism underlying arterial inflammatory function might lead to the development of novel therapeutic strategies. Angiotensin II (AngII) is implicated in atherogenesis by activating the vascular inflammation system, mainly through monocyte chemotaxis. Therefore, we hypothesized that AngII increases plaque size and promotes destabilization of established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 49 publications
4
72
0
Order By: Relevance
“…In a previous study that examined the therapeutic effects of anti-atherosclerotic drugs 17) , an excess of 60 animals was needed per group to ensure that the studies were adequately powered. To overcome this problem, we performed chronic infusion of angiotensin Ⅱ in addition to HFD feeding in ApoE −/− mice because this has been used to enhance the features of atherogenesis, such as monocyte-mediated inflammation, lipid accumulation, and MMP activation 22,24) . We found that chronic angiotensin Ⅱ infusion could increase the incidence of plaque rupture from less than 1 rupture per plaque (authors' unpublished observation) to 3.4 per plaque (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study that examined the therapeutic effects of anti-atherosclerotic drugs 17) , an excess of 60 animals was needed per group to ensure that the studies were adequately powered. To overcome this problem, we performed chronic infusion of angiotensin Ⅱ in addition to HFD feeding in ApoE −/− mice because this has been used to enhance the features of atherogenesis, such as monocyte-mediated inflammation, lipid accumulation, and MMP activation 22,24) . We found that chronic angiotensin Ⅱ infusion could increase the incidence of plaque rupture from less than 1 rupture per plaque (authors' unpublished observation) to 3.4 per plaque (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 weeks on the experimental diets, all mice received angiotensin Ⅱ (1.9 mg/kg per day) for 4 weeks 22,24) . Angiotensin Ⅱ was dissolved in phosphate-buffered saline and loaded into miniosmotic pumps (Alzet, Cupertino, CA) according to the recommendations of the manufacturer.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…23,24 The chronic infusion of Ang II increases arterial MCP-1 transcription and translation, both of which are upregulated within the aged aortic wall. 25 Moreover, in older nonhuman primates and rodents, arterial wall, angiotensin-converting enzyme, and Ang II are increased. 8,16 Furthermore, in rodents, chronic angiotensin-converting enzyme inhibition dramatically retards multiple features of age-associated aortic remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␤ was induced by MCP-1 in human monocytes (Jiang et al, 1992), and the induction after focal brain ischemia was significantly reduced in MCP-1-knockout mice (Hughes et al, 2001). 7ND gene transfer significantly reduced several cytokines, including IL-1␤, TNF-␣, interleukin 6, transforming growth factor ␤, and MCP-1 in aorta (Inoue et al, 2002, Ni et al, 2004 and TNF-␣, transforming growth factor ␤, and MCP-1 in ischemic heart from 1 to 7 days after myocardial infarction (Hayashidani et al, 2003). Therefore, the anti-MCP-1 approach appears to suppress the induction of proinflammatory cytokines and thereby inhibit the upregulation of adhesion molecules and inflammatory cell infiltrations, which would result in attenuation of tissue injury by brain ischemia.…”
Section: Fig5mentioning
confidence: 95%